Pharmacotherapeutic Potential of Aloe secundiflora against Colorectal Cancer Growth and Proliferation - John M. Macharia; Veronica Ngure; Barnabás Emődy; Bence Király; Zsolt Káposztás; Nóra Rozmann; Attila Erdélyi; Bence Raposa (MDPI AG, 2023)
Aloe species are widespread and diverse in African ecosystems, and this commonly correlates to their habitual use as reservoirs of herbal medicine. The side effects associated with chemotherapy and the development of antimicrobial resistance to empirically used antimicrobial drugs are substantial, paving the way for novel phytotherapeutic approaches. This comprehensive study aimed to evaluate and present Aloe secundiflora (A. secundiflora) as a compelling alternative with potential benefits in colorectal cancer (CRC) treatment. Important databases were systematically searched for relevant literature, and out of a large collection of 6421 titles and abstracts, only 68 full-text articles met the inclusion criteria. A. secundiflora possesses an abundant presence of bioactive phytoconstituents in the leaves and roots, including anthraquinones, naphthoquinones, phenols, alkaloids, saponins, tannins, and flavonoids, among others. These metabolites have proven diverse efficacy in inhibiting cancer growth. The presence of innumerable biomolecules in A. secundiflora signifies the beneficial effects of incorporating the plant as a potential anti-CRC agent. Nonetheless, we recommend further research to determine the optimal concentrations necessary to elicit beneficial effects in the management of CRC. Furthermore, they should be investigated as potential raw ingredients for making conventional medications.